A finite element analysis on combined convection and conduction in a channel with a thick walled cavity - Rahman, Md Mustafizur; Oztop, Hakan F.; Mekhilef, Saad; Saidur Rahman; Chamkha, Ali J.; Ahsan, Amimul; Al-Salem, Khaled S. (Emerald Group Publishing, 2014)
Purpose: The purpose of this paper is to examine the effects of thick wall parameters of a cavity on combined convection in a channel. In other words, conjugate heat transfer is solved. Design/methodology/approach: Galerkin weighted residual finite element method is used to solve the governing equations of mixed convection. Findings: The streamlines, isotherms, local and average Nusselt numbers are obtained and presented for different parameters. It is found heat transfer is an increasing function of dimensionless thermal conductivity ratio. Originality/value: The literature does not have mixed convection and conjugate heat transfer problem in a channel with thick walled cavity.